Interpretazione e mediazione in un sistema di cura interculturale. Pratiche di esclusione e pratiche di inclusione dei pazienti migranti - Farini, Federico (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
This paper examines the joint activity of translation and intercultural mediation carried out by interpreters in health care contexts. The analysis presented concerns not only the linguistic aspects, but also the processes of inclusion and exclusion of migrant patients, produced in consequence of the cultural effects of mediation. The corpus of data we analyze consists of physician-patient interactions mediated by an interpreter, collected in 2010 in public health facilities in the provinces of Modena and Reggio Emilia. The following question guided our analysis: “Does interlingual and intercultural mediation promote or discourage active participation by the migrant patient?” Our analysis confirms that the interpreters not only act as facilitators of language, but above all as coordinators of communication, and for this reason are considered as interlingual and intercultural mediators. The different ways in which the mediators coordinate these interactions affect the participation of migrant patients, which can be rendered more or less “invisible” in accordance with the choices of translation.